The World Bank: Structure and policies - Gilbert, C (Cambridge University Press, 2000)
Twelve papers argue that the World Bank's greatest asset is its accumulated knowledge and experience of the development process, and propose that it organize itself around the concept of a "Knowledge Bank." Papers focus on an overview of some major issues of the World Bank; positioning the World Bank; the World Bank and poverty reduction in the past, present, and future; why the World Bank should be involved in development research; the challenges of multilateralism and governance; lessons from the 1980s on the World Bank and structural adjustment; the implications of foreign aid fungibility for development assistance; aid, growth, the incentive regime, and poverty reduction; microeconomic evidence on aid, policies, and investment productivity; the World Bank and sector investment programs in Africa; the World Bank, conditionality, and the Comprehensive Development Framework; and the current debates over conditionality, dependence, and coordination in aid policy. Gilbert is at the Free University, Amsterdam. Vines is at Balliol College, University of Oxford. Index.